COVID‐19 booster dose vaccination of healthcare workers in Qatar: A web‐based cross‐sectional survey - Amudha Pattabi; Ananth Nazarene; Sejo Varghese; Abdulqadir Nashwan; Reena Philip; Ramya Munuswamy; Kalpana Singh (Wiley, 2023)
Abstract Background Vaccines are an important public health measure and effective strategy to protect the population from COVID‐19. Front‐line healthcare personnel should receive priority in vaccination programs. However, the reported hesitancy among healthcare workers (HCWs) toward the COVID‐19 vaccines cannot be ignored. It widely influences the level of vaccine hesitancy in the general population. Hesitancy, fear, and anxiety were documented in first and second rounds of COVID‐19 vaccination. This study assessed the acceptance of COVID‐19 booster doses among the HCWs in Qatar. Methods A web‐based cross‐sectional online survey was conducted using the 7C Vaccine Readiness Scale to evaluate the preparedness of the HCWs to receive COVID‐19 vaccines. Descriptive and inferential statistics were used to identify factors associated with preparedness for vaccination. Results A total of 382 participants completed the survey. Allied health professionals scored the least on the readiness score (−7.0 ± 9.9) compared to the physicians (3.1 ± 7.2) and nurses (3.0 ± 7.8). Physicians scored higher on confidence (58.8%), calculation (64.7%), and complacency (60.8%). Nurses scored higher on constraints (51.6%), collective responsibility (62.7%), and compliance (39.1%), and allied health professionals scored higher on (67.9%) conspiracy. There was a significant association between readiness score and not being infected with COVID‐19, post‐vaccine symptom experience, and hesitancy for the initial two doses. Conclusion This study reports higher complacency and constraints with the perception of lower risks and the lack of interest in taking collective responsibility among the HCWs. Addressing vaccine hesitancy among them is critical to ensure successful vaccination campaigns and promote community safety during future pandemics.